Registry to investigate the efficacy and safety of the VenaBlock© VeIn SEaling system for VaRicose veins in SingApore – Six months results of the RIVIERA trial. (December 2021) - Linn, YL; Yap, CJQ; Soon, SXY; Chan, SL; Khoo, VBX; Chong, TT; Tang, TY
Background: The Venablock © Venous Closure System (Invamed, Ankara, Turkey) is a novel cyanoacrylate-based non-thermal non-tumescent embolization device to block refluxing truncal veins for chronic venous insufficiency and varicose veins. The aim was to prospectively evaluate the safety and 6 months efficacy of Venablock © for the treatment of primary great saphenous vein (GSV) and small saphenous vein (SSV) incompetency in a multi-ethnic cohort from Singapore. Methods: This was a single arm, single investigator prospective study of 29 patients (39 limbs, 39 truncal veins) recruited over a 5-month period (August 2019 to February 2020), who were treated with the Venablock © device at a tertiary vascular unit in Singapore. Patients with symptomatic varicose veins (C2–6) and had truncal reflux > 0.5 second on venous Duplex ultrasound were included. Follow-up occurred at 2 weeks, 3 and 6 months with dedicated quality of life questionnaires and a targeted Duplex ultrasound performed to check for continued venous occlusion. Result: Mean age was 61.4 (±11.0) years and mean BMI was 26.2 (±5.7) kg/m 2 . 11/29 (37.9%) were males. Most common CEAP class treated was 2 (12/29, 41.3%). Mean diameter of treated GSV was 5.7 (±2.0) mm, 4.8 (±1.7) mm and 4.2 (±1.3) mm for the proximal, mid and distal above knee segments respectively. Mean time from access puncture to sheath removal was 23.4 (±10.0) mins. Vein occlusion at 2 weeks, 3 and 6 months was 39/39 (100%), 39/39 (100%) and 36/37 (97.2%) respectively. 5/29 (17.2%) developed puncture site infections, of which 3/29 (7.7%) required formal surgical drainage. 3/29 (7.7%) developed phlebitis. At 6 months, revised Venous Clinical Severity Score improved from 5.2 (±3.5) to 2.1 (±2.9; p < .001); EuroQol-5 Dimension score, from 7.4 (±2.1) to 5.7 (±1.4; p < .001); Aberdeen Varicose Vein Questionnaire score, from 18.1 (±15.5) to 7.9 (±8.9; p = .007); and Chronic Venous Insufficiency Questionnaire, from 18.6 (±16.2) to 4.5 (±6.3; p < .001). Conclusion: Venablock © is a safe and efficacious option of treating truncal venous insufficiency in a multi-ethnic Asian cohort from Singapore in the short term. There is a significant improvement in QoL. Longer follow-up is required to assess the durability of this technique, in particular the higher puncture site infection rates observed compared to other glue-based therapies.